Madam Belle : sex, money, and influence in a Southern brothel - Wall, Maryjean (University Press of Kentucky, 2014)
Belle Brezing made a major career move when she stepped off the streets of Lexington, Kentucky, and into Jennie Hill''s bawdy house -- an upscale brothel run out of a former residence of Mary Todd Lincoln. At nineteen, Brezing was already infamous as a youth steeped in death, sex, drugs, and scandal. But it was in Miss Hill''s ""respectable"" establishment that she began to acquire the skills, manners, and business contacts that allowed her to ascend to power and influence as an internationally known madam. In this revealing book, Maryjean Wall offers a tantalizing true story of vice and power